Perbedaan Tingkat Stres Kerja Antara Perawat Shift Pagi, Siang Dan Malam Bagian Rawat Inap Kelas Vip Sampai Vvip Rumah Sakit Pku Muhammadiyah Surakarta - Sulastri, Sulastri; , dr. Hardjanto MS.Sp.OK; , Anisa Catur Wijayanti, SKM., M.Epid (2016)
Nurse work takes care of to lodge within doors pain was not quit of arrangement of office hours recognized by shift work. Work stress to represent the individual psychological respon to demand at work claiming someone to adapt in overcoming it. This research was purpose to identify the difference of work stres level between nurses of morning, noon and night shift part of taking care of to lodge PKU Muhammadiyah Surakarta Hospital. This research was using analytic observational method with cross sectional approach. This research population was the nurses take care of to lodge was working morning, noon and night shift at Multazam, Umar and Abu Bakar room of PKU Muhammadiyah Surakarta Hospital amounting to 50 nurses. The sampling technique was using exhaustive sampling. Meanwhile, data was analyzed by using Kruskal-Wallis shows that there was significant differences work stress level between morning, noon and night shift at part of taking care of to lodge nurses PKU Muhammadiyah Surakarta Hospital p value = 0,001 with the highest stress level at night shift with mean rank value 56,92. Suggested that a nurse shall do the rest which enough after working for to take care of the condition of physical and bounce and also apply the healthy life pattern as prevention form the happening of stress.